Hybridization Approach to Identify Salicylanilides as Inhibitors of Tubulin Polymerization and Signal Transducers and Activators of Transcription 3 (STAT3) - Marta Gargantilla; Leentje Persoons; Tereza Kauerová; Natalia del Río; Dirk Daelemans; Eva-María Priego; Peter Kollar; María-Jesús (MDPI AG, 2022)
The superimposition of the X-ray complexes of cyclohexanediones (i.e., TUB015), described by our research group, and nocodazole, within the colchicine binding site of tubulin provided an almost perfect overlap of both ligands. This structural information led us to propose hybrids of TUB015 and nocodazole using a salicylanilide core structure. Interestingly, salicylanilides, such as niclosamide, are well-established signal transducers and activators of transcription (STAT3) inhibitors with anticancer properties. Thus, different compounds with this new scaffold have been synthesized with the aim to identify compounds inhibiting tubulin polymerization and/or STAT3 signaling. As a result, we have identified new salicylanilides (6 and 16) that showed significant antiproliferative activity against a panel of cancer cells. Both compounds were able to reduce the levels of p-STAT3Tyr705 without affecting the total expression of STAT3. While compound 6 inhibited tubulin polymerization and arrested the cell cycle of DU145 cells at G2/M, similar to TUB015, compound 16 showed a more potent effect on inhibiting STAT3 phosphorylation and arrested the cell cycle at G1/G0, similar to niclosamide. In both cases, no toxicity towards PBMC cells was detected. Thus, the salicylanilides described here represent a new class of antiproliferative agents affecting tubulin polymerization and/or STAT3 phosphorylation.